Chemical composition and potential for antimicrobial properties of \(Magnolia citrata\) Noot. & Chalermglin (Magnoliaceae) essential oils in Central Highlands of Vietnam - Hai Dang, Nguyen; Ngoc Anh, Luu Dam; Bao Ngan, Tu; Anh Huyen, Nguyen; Huong, Bui Van; Arpino, Patrick (Academia Journal of Biology, 2023)
Magnolia citrata Noot. & Chalermglin was collected in the Central Highlands of Vietnam and examined for its essential oils’ chemical compositions and antimicrobial activities. The essential oils were obtained from the leaves, twigs, and stem barks of M. citrata using hydrodistillation, then analyzed using Gas Chromatography-Mass Spectrometry (GC-MS) and evaluated for antimicrobial activities. The yields of essential oils were 0.06, 0.51, and 0.16% from twigs, leaves, and stem barks, respectively. A total of forty-three compounds were identified in essential oils, accounting for 98.0, 98.8, and 98.4%, respectively. The major constituents of the oils from leaves and twigs varied slightly. Accordingly, geranial (23.1%), neral (22.5%), linalool (22.5%), and sylvestrene (6.3%) were found in the leaves, while geranial (30.9%), neral (29.6%), sylvestrene (11.8%), and linalool (6.1%) were found in the twigs. In addition, sylvestrene was the major component comprising 51.8% of the stem bark oils. Other compounds present in high quantities in this oil included safrole (11.6%), geranial (6.9%), sabinene (6.9%), and neral (6.6%). The antimicrobial activities of the essential oil samples were tested against six bacterial strains and one yeast strain for the first time. The results indicated that essential oils from M. citrata had strong antimicrobial activities. At the concentration of 64 µg/mL, the essential oils from its three parts effectively inhibited the growth of the Gram-positive bacteria Enterococcus faecalis, Staphylococcus aureus, and Bacillus cereus, as well as the yeast Candida albicans. Against the Gram-negative bacteria, including Escherichia coli, Pseudomonas aeruginsa, and Salmonella enterica, the effective concentrations of the oils for inhibition varied from 128 µg/mL to 256 µg/mL.